Research on Dynamic Assessment of Proprioceptive Function Recovery and Optimization of Rehabilitation Training Programs After Sports Injuries - Gao, Penghao; Liu, Jing (Pinnacle Academic Press Proceedings Series, 2026)
Sports injuries are common in athletic participation, and the recovery of proprioceptive function is crucial for restoring motor control, preventing re‑injury, and enabling safe return to sport. This study focuses on the dynamic assessment of proprioceptive function recovery after different types of sports injuries and on the optimization of corresponding rehabilitation training programs. First, the research background, objectives, current domestic and international research status, and methodological framework are outlined, including assessment design, participant selection, and data analysis strategies. Second, the theoretical basis of proprioceptive function is introduced, covering its definition, physiological mechanisms, and the specific ways in which ligament, muscle, and joint injuries impair proprioceptive feedback and neuromuscular regulation. On this basis, a dynamic evaluation system and model for monitoring proprioceptive recovery over time are constructed, integrating quantitative tests, functional performance measures, and clinical scales. Furthermore, the basic principles, commonly used techniques, and program optimization strategies for proprioceptive-oriented rehabilitation training are analyzed, emphasizing progression, individualization, and task specificity. An empirical study is conducted through typical case analyses, in which different rehabilitation schemes are compared, and key factors influencing recovery efficiency are summarized. Finally, the main conclusions are presented, limitations of the current work are discussed, and directions for future research on assessment technology and training protocols are proposed, aiming to provide theoretical support and practical guidance for sports injury rehabilitation.